2018
DOI: 10.1016/j.dcn.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Brain areas associated with numbers and calculations in children: Meta-analyses of fMRI studies

Abstract: Children use numbers every day and typically receive formal mathematical training from an early age, as it is a main subject in school curricula. Despite an increase in children neuroimaging studies, a comprehensive neuropsychological model of mathematical functions in children is lacking. Using quantitative meta-analyses of functional magnetic resonance imaging (fMRI) studies, we identify concordant brain areas across articles that adhere to a set of selection criteria (e.g., whole-brain analysis, coordinate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
190
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 210 publications
(220 citation statements)
references
References 108 publications
27
190
0
3
Order By: Relevance
“…Furthermore, people with higher egoistical motivation, who more frequently violate social norms, have weaker connectivity between these regions (Hein et al, ). This is consistent with the hypothesis that the cingulate gyrus and insula are involved in conversion of affective goals into cognitive goals (Arsalidou & Pascual‐Leone, ) as a feeling of effort in cognitively demanding situations (Arsalidou et al, ). A generic role of the insula as part of a salience network has been suggested (Menon & Uddin, ; Uddin, ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, people with higher egoistical motivation, who more frequently violate social norms, have weaker connectivity between these regions (Hein et al, ). This is consistent with the hypothesis that the cingulate gyrus and insula are involved in conversion of affective goals into cognitive goals (Arsalidou & Pascual‐Leone, ) as a feeling of effort in cognitively demanding situations (Arsalidou et al, ). A generic role of the insula as part of a salience network has been suggested (Menon & Uddin, ; Uddin, ).…”
Section: Discussionsupporting
confidence: 90%
“…A contrast analysis was performed on the thresholded ALE maps of social norm representation and norm violation categories to identify concordance that was common (i.e., conjunction) and different for these categories. Because ALE maps are already thresholded for multiple comparisons a threshold of uncorrected 0.01, with 5000 permutations, minimum volume 50 mm 2 was used (e.g.,Arsalidou, Pawliw-Levac, Sadeghi, & Pascual-Leone, 2017;Sokolowski, Fias, Mousa, & Ansari, 2017).…”
mentioning
confidence: 99%
“…In the current study we tested whether numerical perception and different numerical operations activate overlapping brain areas, as previously suggested by coarse-scale quantitative meta-analyses (Arsalidou and Taylor, 2011;Arsalidou et al, 2018) or whether a finer-scale pattern of sub-regional specialization within the parietal cortex can be revealed by the enhanced spatial resolution provided by ultra-high field fMRI combined with cortical surface-based analysis. To more precisely localize the observed activation foci and shed new light on their potential relation with known sub-regions of macaque cortex, we further related activations to anatomical and functional markers on the cortical surface, with the help of two atlases based on curvature and visual topography.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, two meta-analyses quantified the degree of overlap of the parietal activations elicited by different numerical tasks and concluded that the very same regions are recruited, namely the inferior and superior parietal lobules (IPL and SPL) which delimit the intraparietal sulcus (IPS), during calculation and non arithmetics-related numerical task, both in adults (Arsalidou and Taylor, 2011) and in children (Arsalidou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons related to the representation of visual quantity have been described in the parietal cortex of macaques (Nieder et al, 2002;Nieder, 2013;Roitman et al, 2007Roitman et al, , 2012. This representation may support simple arithmetic operations that are more fully developed in humans (Fehr et al, 2007;Rosenberg-Lee et al, 2011;Arsalidou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%